Pendekatan internet marketing: strategi pengembangan industri kecil menengah kerajinan - Dahmiri, Dahmiri; Kartika Wulan Bhayangkari, Sylvia; Tiswiyanti, Wiwik (Jurnal Paradigma Ekonomika, 2021)
This study aimed to determine the obstacles handicraft SMEs face in business development and to analyze the development strategy of small and medium handicraft industries with an internet approach. The sample of this research is Handicraft IKM entrepreneurs in districts/cities in Jambi Province. The data collection tool is in interview guides with both craft IKM actors and critical respondents. The types of data required are primary data and secondary data. Preliminary data were collected utilizing interviews and direct observation of SMI actors, while secondary data was obtained from literature and reports from related institutions. The data and information obtained are processed using qualitative data processing methods, then further analyzed to develop priorities for the company. The analytical tools used are Internal Analysis, SWOT Matrix. The results of the study concluded that the craft IKM development strategy with an internet marketing approach could be done by: 1) marketing through the internet in the form of websites, social media (Facebook, Twitter, Instagram), and marketplace; 2) excellent service; 3) simplify the administrative process; 4) create easy hints; 5) Provide affordable fees; 6) Immediately respond to complaints and complaints. Â